Pengembangan Aplikasi Game Edukasi Berbasis Kuis untuk Pengenalan Budaya Yogyakarta kepada Mahasiswa Perantau - Christopher, Ryan; Findra Kartika Sari Dewi (Universitas Atma Jaya Yogyakarta, 2025)
The high number of migrant students in Yogyakarta has created a need for an effective solution to introduce them to the local culture, social etiquette, and other essential information in order to prevent culture shock during their stay. One proposed solution is the development of a smartphone-based application designed specifically for students. This application takes the form of an educational game, presented through interactive quizzes that contain informative and instructional content. It offers a variety of topics, including introductions to local culture, Yogyakarta’s social norms, the city's historical background, tourist attractions, and more. This application is expected to serve as an engaging and effective medium for helping students adapt to cultural differences. Moreover, it aims to foster a sense of appreciation, respect, and love for Indonesian culture, particularly the rich cultural heritage of Yogyakarta. Tingginya jumlah mahasiswa perantau di Kota Yogyakarta menimbulkan kebutuhan akan solusi yang efektif untuk memperkenalkan budaya lokal, etika sosial, serta informasi penting lainnya guna mencegah terjadinya culture shock selama masa adaptasi. Salah satu solusi yang diusulkan adalah pengembangan aplikasi berbasis perangkat pintar yang dapat diunduh oleh mahasiswa. Aplikasi ini dirancang dalam bentuk permainan edukatif yang dikemas melalui kuis interaktif, berisi materi-materi informatif dan edukatif. Melalui berbagai topik yang ditawarkan, seperti pengenalan budaya lokal, etika pergaulan masyarakat Yogyakarta, sejarah kota, destinasi wisata, dan aspek penting lainnya, aplikasi ini diharapkan dapat menjadi sarana yang menarik dan efektif bagi mahasiswa dalam proses adaptasi budaya. Lebih jauh, aplikasi ini bertujuan untuk menumbuhkan rasa cinta, penghargaan, dan apresiasi terhadap kebudayaan Indonesia, khususnya budaya yang ada di Kota Yogyakarta.